The aadA Gene of Plasmid R100 Confers Resistance to Spectinomycin and Streptomycin in Myxococcus xanthus - Magrini, Vincent (American Society for Microbiology, 1998)
Plasmids with the aadA gene from plasmid R100, which confers resistance to the aminoglycosides spectinomycin and streptomycin in Escherchia coli, can be introduced into wild-type Myxococcus xanthus, strain DK1622, by electroporation. Recombinant M. xanthus strains with integrated plasmids carrying the aadA gene acquire resistance to high levels of these antibiotics. Selection for aadA in M. xanthus can be carried out independently of, or simultaneously with, selection for resistance to kanamycin. The kinds and frequencies of recombination events observed between integrative plasmids with aadA and the M. xanthus chromosome are similar to those observed after the transformation of yeast. Cleavage of integrative plasmid DNA at a site adjacent to a region of homology between the plasmid and the M. xanthus genome favors the targeted disruption of M. xanthus genes by allele replacement.